2016
DOI: 10.3233/bmr-160665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pilates and trunk strengthening exercises on health-related quality of life in women with chronic low back pain

Abstract: An 8-week Pilates program improved HRQOL and reduced functional disability more than either a trunk strengthening exercise program or controls among women with CLBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 23 publications
0
70
1
7
Order By: Relevance
“…These studies also showed that Clinical Pilates education was customized in different cases, such as low back and neck pain, postural distortions, orthopedic injuries, neurological problems, rheumatic problems, cancer, osteoporosis, osteoarthritis, scoliosis, and pregnancy apart from the cases of healthy individuals 2,5,9,10…”
Section: Introductionmentioning
confidence: 98%
“…These studies also showed that Clinical Pilates education was customized in different cases, such as low back and neck pain, postural distortions, orthopedic injuries, neurological problems, rheumatic problems, cancer, osteoporosis, osteoarthritis, scoliosis, and pregnancy apart from the cases of healthy individuals 2,5,9,10…”
Section: Introductionmentioning
confidence: 98%
“…Os estudos de forma geral mostraram efeitos positivos para o MP em pacientes com dor lombar crônica não especifica. Os principais benefícios do método apontados pelos estudos foram principalmente sobre o alivio da dor (CRUZ-DÍAZ et al, 2018;CRUZ-DÍAZ et al, 2015;MACHADO et al, 2017;MIYAMOTO et al, 2018;NATOUR et al, 2015;VALENZA et al, 2017), a maior na capacidade funcional (CRUZ-DÍAZ et al, 2018;CRUZ-DÍAZ et al, 2015;KOFOTOLIS et al, 2016;MACHADO et al, 2017;MIYAMOTO et al, 2018;NATOUR et al, 2015;VALENZA et al, 2017) principalmente em pessoas idosas, aumento da flexibilidade e mobilidade (CRUZ-DÍAZ et al, 2015;MACHADO et al, 2017;VALENZA et al, 2017), melhora no equilíbrio corporal (CRUZ-DÍAZ et al, 2015;LOPES et al, 2017;VALENZA et al, 2017), aumento da qualidade de vida (KOFOTOLIS et al, 2016;NATOUR et al, 2015), maior resistência muscular (MACHADO et al, 2017), e redução da cinesiofobia (CRUZ-DÍAZ et al, 2018) (tabela1). Sobre os estudos selecionados para a pesquisa, a maioria realizou ensaios clínicos randomizados (CRUZ-DÍAZ et al, 2018;KOFOTOLIS et al, 2016;MIYAMOTO et al, 2018;MOSTAGI et al, 2015;NATOUR et al, 2015;VALENZA et al, 2017), dois ensaio controlado aleatório único e cego (CRUZ-DÍAZ et al, 2015;LOPES et al, 2017) apenas um estudo de coorte prospectivo observacional (MACHADO et al, 2017).…”
Section: Resultsunclassified
“…The results showed that Pilates was effective for the reduction of pain and disability in individuals with non-specific LBP corroborating with similar results found in the literature 7,30,31 . Kofotolis, Kellis, Vlachopoulos, Gouitas, Theodorakis 32 reported that Pilates was more effective than trunk strengthening in increasing the quality of life and decreasing the functional disabilities after an 8-week protocol and the effects were retained for a three-month follow-up 32 . Studies that evaluated the effectiveness of a Pilates protocol compared to general exercises or self-management for eight weeks concluded that the method was more effective in reducing pain, disability, flexibility and balance in individuals with chronic LBP 21,22 .…”
Section: Discussionmentioning
confidence: 99%